Self-generated encryption model of acoustics - Etem, Taha; Kaya, Turgay (Elsevier Sci Ltd, 2020)
True Random Number Generator is a popular research area as a result of its encryption usage. Encrypting any data with a random source ensures security of information. The aim of this paper is to develop a self-generated True Random Number for audio encryption. To this end, an audio encryption system was created. Digital audio data is converted into binary form. XOR operation is performed to design Random Number Generator. NIST 800-22 Test Suite and TestU01 are applied on bit stream. Original data and encryption key are evaluated in case of randomness. Encryption of audio is made by generated bits. This paper proves that, a self-generated audio encryption system can be implemented. Statistical analyses and data distributions shows that encryption process with self-generation is successful. In this work, an audio encryption model of self-generated True Random Number is proposed. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: True Random Number Generator; Audio Encryption; Information Security